Protective Effects of Physalis angulata on Podocythopathies Through B-Cell-Activating Factor Inhibition in Doxorubicin-Induced Nephrotic Syndrome Rat Model - Astrid K. Kardani; Loeki E. Fitri; Nur Samsu; Krisni Subandiyah (Biomedicines)
Background/Objectives: Nephrotic syndrome, a glomerular disease caused by podocyte dysfunction, is characterized by proteinuria, hypoalbuminemia, edema, and hyperlipidemia. Current treatment relies on corticosteroids, which carry the risk of long-term side effects. Physalis angulata has potential as an adjunct therapy for immune-mediated kidney injury. This study aims to evaluate the effects of Physalis angulata extracts on anti-nephrin IgG, IL-4, and podocytopathy through BAFF inhibition in a doxorubicin-induced nephrotic syndrome rat model. Methods: This experimental study involved 36 Sprague–Dawley rats divided into control and treatment groups. The treatment groups received Physalis angulata extract at doses of 500 mg/kgBW, 1500 mg/kgBW, and 2500 mg/kgBW, or in combination with prednisone, alongside a group receiving prednisone monotherapy. Podocytopathy was assessed using proteinuria, nephrin, podocalyxin, and GLEPP-1. Proteinuria was measured using spectrophotometry. Serum BAFF levels, renal IL-4, urinary nephrin, and urinary podocalyxin were analyzed using ELISA. Renal nephrin, renal podocalyxin, GLEPP-1, and BAFF expression were evaluated by immunofluorescence microscopy. The data were analyzed using SPSS 25. Results: The results showed significant reductions in proteinuria, serum BAFF levels, renal BAFF expression, anti-nephrin IgG, IL-4, urinary nephrin, and urinary podocalyxin, along with significant increases in GLEPP-1, renal nephrin, and renal podocalyxin expression, in all treatment groups compared to the nephrotic syndrome control group. The combination of Physalis angulata at 2500 mg/kgBW with prednisone demonstrated the best effects. Conclusions: Physalis angulata shows promise as an adjuvant therapy for nephrotic syndrome by improving podocytopathy through BAFF inhibition. Further research is needed to evaluate its long-term safety, optimize dosing, and explore clinical applications in humans.